2015
DOI: 10.1515/ijamh-2014-0037
|View full text |Cite
|
Sign up to set email alerts
|

Sleep in university students across years of university education and gender influences

Abstract: Gender and years of university education influence sleep among university students both separately and concomitantly.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
18
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 31 publications
(21 citation statements)
references
References 12 publications
3
18
0
Order By: Relevance
“…Additionally, lack of awareness about sleep health in developing societies is common [18]. The lesser awareness might lead to contrived low sensitivity of this component in such societies [4, 10]. …”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Additionally, lack of awareness about sleep health in developing societies is common [18]. The lesser awareness might lead to contrived low sensitivity of this component in such societies [4, 10]. …”
Section: Discussionmentioning
confidence: 99%
“…The validation of the tool in the Nigerian students found that the global PSQI and component scores (except daytime dysfunction and sleep medicine) were significantly higher among insomniacs [7]. The relatively less contribution of the PSQI component of daytime dysfunction and sleep medicine to internal consistency, homogeneity, and discriminative validity in Afro-Asian populations [4, 7, 10] is interesting and need to be explored further. This may help further increase the utility of the tool in these populations and understanding of sleep health construct in these societies.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This is a secondary analysis of the data presented in our previous paper. More details about participant characteristics and methods of data collection are documented therein (Manzar et al 2015 ).…”
Section: Methodsmentioning
confidence: 99%
“…Difficulties with sleeping are an endemic problem among college students in competitive academic environments (Manzar et al 2015 ). Sleep problems are often part of a feedback cycle, being an important result of as well as the cause of many of the challenges of university life.…”
Section: Introductionmentioning
confidence: 99%